Clima organizacional y calidad de atención en la Municipalidad Provincial de Ucayali Contamana 2023 - Mucha Ruiz, Wilson Jhony (2024)
The study objective of the report was to determine the relationship between the organizational climate and quality of care in the Provincial Municipality of Ucayali Contamana 2023. We opted for an applied type study accompanied by a non-experimental design, taking as a sample 89 workers, to whom a questionnaire was applied for the collection of information. Obtaining as results that, the organizational climate in this institution is qualified as inadequate by 50% of the respondents, since most of the workers express job insecurity, dissatisfaction with the schedule and lack of involvement in decisions and see limited opportunities for professional growth. On the other hand, the quality of care in the Municipality is rated as good by 50% of the sample, since they offer the requested service in adequate times and always have clear information about the services they provide, show a high predisposition to resolve conflicts in their work, respond quickly to the needs of users, and always maintain an attitude of respect towards their colleagues. Finally, it was determined that there is a relationship between the variables, with a correlation coefficient of 0.517 and a statistical significance of 0.00 (positive mean).